2022
DOI: 10.1515/applirev-2021-0171
|View full text |Cite
|
Sign up to set email alerts
|

Immersing learners in English listening classroom: does self-regulated learning instruction make a difference?

Abstract: Drawing on self-regulated learning (SRL) theory, this quasi-experimental research examined the effectiveness of SRL listening instruction and its influence on L2 listening motivation and strategy use. Quantitative data were collected from 80 undergraduate students who enrolled in an English listening course at a Chinese university. The experimental group (N = 40) received 17-week SRL English listening instruction, whereas the control group (N = 40) received traditional product-oriented listening instruction. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Mohammadi et al (2020) found that students who were taught SRL strategies showed greater improvement in reading comprehension compared with the control group. Xu and Luo (2022) found that SRL training improved listening comprehension in university students. Theobald (2021) conducted a meta-analysis of studies on SRL and academic achievement and found that SRL interventions had a positive effect on academic achievement, with the effect size being the largest for younger learners.…”
Section: Background Of the Studymentioning
confidence: 95%
“…Mohammadi et al (2020) found that students who were taught SRL strategies showed greater improvement in reading comprehension compared with the control group. Xu and Luo (2022) found that SRL training improved listening comprehension in university students. Theobald (2021) conducted a meta-analysis of studies on SRL and academic achievement and found that SRL interventions had a positive effect on academic achievement, with the effect size being the largest for younger learners.…”
Section: Background Of the Studymentioning
confidence: 95%
“…It was found that English course design based on VR could enhance students' English learning confidence and sense of achievement. Literature [21] investigated the specific impact of selfregulated learning theory on students' English listening courses based on the theory. From the quantitative data analysis of 80 students, it was found that the stronger the students' self-regulated learning ability was, the higher their listening level was, and the English course design based on this theory could effectively improve the students' English listening ability.…”
Section: Introductionmentioning
confidence: 99%
“…Et al. Based on the self-regulation theory, conducted an in-depth examination of the effectiveness of self-study listening teaching and how it affects the motivation and strategy use of L2 listening, and found that SRL listening teaching has a positive impact on students' L2 listening comprehension and perception [15]. Dong, F. Optimized the interactive teaching model of university English under the conditions of computer network and digital technology.…”
Section: Introductionmentioning
confidence: 99%